KELEMBAGAAN PEMASARAN DAN KEMITRAAN KOMODITI SAYURAN Kasus di Desa-Desa di Jawa Tengah dan Sumatera Utara - Lestari Hastuti, Endang (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Institutional of Vegetable Commodity Marketing and Partnership: Cases in Villages of Central Java and North Sumatra. Although agribusiness is the biggest contributor of foreign exchange earnings, however, volume of imported vegetables and fruits tent to increase. This situation triggered some disadvantageous suppression on farm gate prices. The results of the research conducted in villages of Central and North Sumatra showed that national vegetable products could not compete with other country’s products. National trading pattern consisted of wholesale trading, medium scale trading and small scale trading. Marketing cost was relatively high while community’s accessibility on formal financing institutional was quite low. Most traders served partnerships with farmers to maintain supply continuity in the mean time farmers could get capital for input production and marketing security. Consumer’s price was very fluctuate due to perishable natures and it is concentrated in a region. Consequently, relationship functions among agribusiness agents is required as well as storage facilities in the agribusiness centers.
Keywords: Development, Agribusiness, Advanced Commodity, Partnership